In vitro and in vivo uptake studies of PAMAM G4.5 dendrimers in breast cancer. Issue 1 (December 2016) - Oddone, Natalia; Lecot, Nicole; Fernández, Marcelo; Rodriguez-Haralambides, Alejandra; Cabral, Pablo; Cerecetto, Hugo; Benech, Juan
Abstract Background Breast cancer is the second leading cause of cancer death worldwide. Nanotechnology approaches can overcome the side effects of chemotherapy as well as improve the efficacy of drugs. Dendrimers are nanometric size polymers which are suitable as drug delivery systems. To the best of our knowledge, studies on the application of PAMAM G4.5 (polyamidoamine half generation 4) dendrimers as potential drug delivery systems in breast cancer have not been reported. In this work we developed a PAMAM G4.5 dendrimer containing FITC (fluorescein isothiocyanate) dye to study their uptake by murine breast cancer cells and BALB/c mice breast tumors. Results We performed a reaction between FITC and PAMAM G4.5 dendrimers which were previously derivatized with piperazine (linker molecule), characterized them by1 H NMR (proton nuclear magnetic resonance) spectroscopy and MALDI-TOF (matrix-assisted laser desorption/ionization- time-of-flight) mass spectrometry. The experimental data indicated that 2 FITC molecules could be bound covalently at the PAMAM G4.5 dendrimer surface, with 17 FITC molecules probably occluded in PAMAM dendrimers cavity. PAMAM-FITC dendrimer (PAMAM G4.5-piperazinyl-FITC dendrimer) size distribution was evaluated by DLS (dynamic light scattering) and TEM (transmission electron microscopy). The nanoparticle hydrodynamic size was 96.3 ± 1.4 nm with a PdI (polydispersion index) of 0.0296 ± 0.0171, and the size distribution measured by TEM was 44.2 ± 9.2 nm. PAMAM-FITC dendrimers were neither cytotoxic in 4T1 cells nor hemolytic up to 24 h of incubation. In addition, they were uptaken in vitro by 4T1 cells and in vivo by BALB/c mice breast tumors. PAMAM G4.5-piperazinyl-FITC dendrimer intracellular distribution was observed through histologic analysis of the tumor by laser confocal microscopy. Conclusion These results indicate that PAMAM G4.5 dendrimers enter tumor tissue cells, being good candidates to be used as antitumor drug delivery systems for breast cancer treatment and diagnosis.